2015
DOI: 10.1016/j.molp.2015.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Tribenuron-Methyl Induces Male Sterility through Anther-Specific Inhibition of Acetolactate Synthase Leading to Autophagic Cell Death

Abstract: Tribenuron-methyl (TM) is a powerful sulfonylurea herbicide that inhibits branched-chain amino acid (BCAA) biosynthesis by targeting the catalytic subunit (CSR1) of acetolactate synthase (ALS). Selective induction of male sterility by foliar spraying of TM at low doses has been widely used for hybrid seed production in rapeseed (Brassica napus); however, the underlying mechanism remains unknown. Here, we report greater TM accumulation and subsequent stronger ALS inhibition and BCAA starvation in anthers than i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 68 publications
6
40
0
Order By: Relevance
“…Thus, an application of ALS-inhibiting gametocides on model plant A. thaliana to replace manual emasculation will be of interest to geneticists when they wish to make many genetic crosses. The results of the present study, combined with previous studies [1214, 23, 24], suggest the possible use of other sulfonylurea chemicals as gametocides for cruciferous plants. The alternate use of other gametocides can resolve the concerns of insensitivity to tribenuron-methyl in some special genotypes.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Thus, an application of ALS-inhibiting gametocides on model plant A. thaliana to replace manual emasculation will be of interest to geneticists when they wish to make many genetic crosses. The results of the present study, combined with previous studies [1214, 23, 24], suggest the possible use of other sulfonylurea chemicals as gametocides for cruciferous plants. The alternate use of other gametocides can resolve the concerns of insensitivity to tribenuron-methyl in some special genotypes.…”
Section: Discussionsupporting
confidence: 82%
“…A high level of MS induced by tribenuron-methyl brings an opportunity for the utilization of heterosis of these minor crops that belong to Brassicaceae including S. alba, E. sativa, C. sativa, C. bursa-pastoris, and M. incana . A previous study also reported that a foliar spray of 15 ng of tribenuron-methyl per plant of A. thaliana had a gametocidal effect [23]. In addition, exposure to trace concentrations of imazethapyr, an ALS-inhibitor, had unstable gametocidal effects on Brassica plants [13] and affected floral organ development and reproduction in A. thaliana [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Full-length cDNA of SID1 were amplified with primer pair SID1(CDs)-OX-F/SID1(CDs)-OX-R and then cloned into pU2301 by Kpn I- BamH I digestion; full-length cDNA of RID1 was amplified with primer pair RID1(cDNA)-OX-F/RID1(cDNA)-OX-R and then cloned into pU2301 by Kpn I- BamH I digestion. To investigate the tissue-specific expression of SID1 , approximately 3-kb promoter fragments of SID1 were amplified from genomic DNA and then cloned into pC2300-EX-GUS [53] to create pSID1 :: GUS . To introduce targeted mutations in SID1 protein, sgRNA:Cas9 expression vector of the SID1 gene was constructed as described previously [44].…”
Section: Methodsmentioning
confidence: 99%
“…Zhao et al (2015) proposed that BCAA starvation induces pollen formation failure and ultimately leads to autophagic cell death in the anthers. The AHAS-inhibitory hybridization agent used in rapeseed (Brassica napus L.) is tibenuron methyl.…”
Section: Partial Male Sterility In Imisun Sunflower: Imazapyr Treatmementioning
confidence: 99%